Kepemimpinan Pendidikan dalam Perspektif Al-Qur’an - Yulia Dessani; Gusmaneli Gusmaneli (Lembaga Pengembangan Kinerja Dosen, 2025)
Leadership has a very important role in determining the success of an organization, especially in the context of Islam which makes the Qur'an and Hadith as the main guidelines. This research aims to explore the concept of Islamic leadership, the ideal characteristics of a leader, and its implications for the life of the people. Using descriptive qualitative method based on literature review, this research analyzes leadership values reflected in Islamic teachings. The results show that Islamic leadership emphasizes the characteristics of Shiddiq (honest), Amanah (trustworthy), Tabligh (conveying the truth), and Fathanah (intelligent), which are the main characteristics of the Prophet Muhammad. In addition, Islamic leadership combines elements of jihad, which is the struggle to obey Allah, and ijtihad, which is the ability to solve the problems of the people based on Islamic values. Effective leadership is not only oriented towards worldly success but also prepares people for the afterlife through justice, high morality, and good organizational management. In conclusion, Islamic leadership offers a holistic approach that integrates spiritual, moral, and social aspects to create a just, prosperous, and blessed society. The findings are expected to be a reference for leaders in implementing Islamic values in various fields, both in the context of organizations and state life.